(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study was conducted to evaluate the prevalence of total aflatoxin (AF) and ochratoxin A (OTA) in poultry feed ingredients under different environmental conditions during the summer and winter seasons, while the hygiene quality of the feed ingredient was assessed through viable fungal count (VFC). Materials and Methods: A total of 288 poultry feed ingredients (n = 96 each) samples were collected from different poultry shops, which were initially analyzed for the presence of AF and OTA through thin layer chromatography (TLC) and then confirmed the contamination concentration through the enzyme-linked immunosorbent assay method. Results: The results of the current study confirmed the incidence of contamination with AF and OTA by TLC and ELISA methods. The contamination level of AF ranged from 26.09 to 50.56 (mean = 41.22 ± 9.45) μg/kg, whereas the contamination level of OTA ranged from 50.13 to 6.21 (mean 42.60 ± 6.21) μg/kg. The contamination level of AF was found to be above the permissible level set by the Food and Drug Administration (20 μg/kg), whereas the contamination level of OTA was below the permissible limits. Moreover, the VFC values were also below the recommended level. The results showed that the association between AF, OTA, and moisture content was significant (p < 0.05). Conclusion: Mycotoxin contamination was significantly (p < 0.05) highest in the winter season. These findings suggested that continuous monitoring regimes might prevent mycotoxin contamination in poultry feed ingredients. Adv. Vet. Anim. Res., 11(1): 107-113, March 2024 http://doi.org/10.5455/javar.2024.k754